2014
DOI: 10.1017/s0003055414000148
|View full text |Cite
|
Sign up to set email alerts
|

Partisanship, Structure, and Representation: The Puzzle of African American Education Politics

Abstract: The 1982 amendments to the Voting Rights Act targeted electoral structures as significant determinants of minority representation. The research regarding electoral structures and representation of constituents, however, has produced conflicting results, and the continued application of some of the provisions set forth in the Voting Rights Act is in doubt. This article addresses the impact of at-large elections on African American representation and reveals a striking and unanticipated finding: African American… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 63 publications
2
28
0
Order By: Relevance
“…Currently, courts are applying “strict scrutiny” to districting that is predominantly based on race (Bowler, Donovan, and Brockington, :17); this may mean that courts will be less likely to prescribe districts as a remedy for vote dilution claims . Furthermore, recent studies have qualified the degree to which district elections increase minority representation over at‐large elections at the local level (Trounstine and Valdini, ; Meier and Rutherford, ). Such circumstances may increase the appeal of cumulative voting plans to remedy VRA claims.…”
Section: Cumulative Votingmentioning
confidence: 99%
“…Currently, courts are applying “strict scrutiny” to districting that is predominantly based on race (Bowler, Donovan, and Brockington, :17); this may mean that courts will be less likely to prescribe districts as a remedy for vote dilution claims . Furthermore, recent studies have qualified the degree to which district elections increase minority representation over at‐large elections at the local level (Trounstine and Valdini, ; Meier and Rutherford, ). Such circumstances may increase the appeal of cumulative voting plans to remedy VRA claims.…”
Section: Cumulative Votingmentioning
confidence: 99%
“…The primary quantity of interest is the marginal effect of conversion estimated at a given level of Latino population, or β2+β3proportionLatino, because if the reform did indeed improve minority electoral outcomes, then the Latino composition of school boards should rise with the size of the Latino population in the district. This is the modeling approach recommended by Engstrom and McDonald (1981) and used in other recent empirical studies on the subject (e.g., Meier and Rutherford 2014; Trounstine and Valdini 2008).…”
Section: Causal Identification Through the Cvramentioning
confidence: 99%
“…Although there is substantial evidence that ward elections for local office result in greater representation for Black and Latino voters (Davidson and Grofman 1994; Davidson and Korbel 1981; Engstrom and McDonald 1981; Karnig and Welch 1982; Leal, Martinez‐Ebers, and Meier 2004; Marschall, Ruhil, and Shah 2010; Meier et al. 2005; Molina Jr. and Meier 2018; Moncrief and Thompson 1992; Polinard 1994; Robinson and England 1981; Stewart, England, and Meier 1989; Trounstine and Valdini 2008), a number of additional studies have found no effect (Bullock and MacManus 1987; Cole 1974; Fraga 2009; MacManus 1978; Welch 1990), with still others that posit a negative association between ward elections and minority electoral success (Meier and Rutherford 2014; Welch and Karnig 1978).…”
mentioning
confidence: 99%
“…However, the argument against MMDs has several shortcomings. First, it downplays the historical role of gerrymandering, literacy tests, and the other institutions and processes designed to thwart the election of racial and ethnic minorities in MMDs and SMDs (Hasen 2004;Winburn 2008;Meier and Rutherford 2014). Second, it does not fully consider the effects of the concentration of African American voters in urban areas (Moncrief and Thompson 1992;Trounstine and Valdini 2008), and it underestimates the importance of majorityminority districts in facilitating minority candidacies in both SMDs and MMDs (Lenz and Pritchard 1991;Lublin 1997;Hadley, Grofman, and Arden 1998;Swers and Rouse 2011).…”
Section: Is District Magnitude An Impediment To the Election Of Africmentioning
confidence: 99%